SISTEM INFORMASI PENGGAJIAN KARYAWAN PADA PT. INDAH MANDIRI SARI - Osella Natasya Ginting; Marlyna Infryanty Hutapea; Gortap Lumbantoruan (TAMIKA: Jurnal Tugas Akhir Manajemen Informatika & Komputerisasi Akuntansi, 2021)
Indah Mandiri Sari is a company engaged in the payment of electricity in collaboration with PT. PLN. This company uses a system manually on the payroll of its employees. Where in the application of this payroll system there are several problems. There are obstacles that occur, namely in terms of calculating salaries, fines, loans, allowances, and salary reports that must be recalculated from each employee, and the storage of payroll files requires more space. With the above reasons, the authors provide an alternative solution to the problem by creating a systematic and computerized employee payroll information system. This paper will also explain the stages of work, starting from the analysis, planning, design process using Microsoft Visual Studio 2010 and Microsoft Access 2007. The purpose of this study is to build an information system that will help the employee payroll process to reduce errors in making salary reports. employees. With this employee payroll information system will be able to minimize the constraints that occurred in the previous system and assist in the completion of employee salary reports and reports are stored properly.